The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1996
DOI: 10.1007/bf01709563
|View full text |Cite
|
Sign up to set email alerts
|

Initial postoperative serum lactate levels predict survival in children after open heart surgery

Abstract: Initial postoperative serum lactate levels after pediatric open heart surgery may be predictive of outcome. Lactate levels are also higher in patients who go on to develop multiple organ system failure. Elevated postoperative lactate levels may reflect intraoperative tissue hypoperfusion, and measures aimed at increasing oxygen delivery, with normalization of lactate, may improve patient outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(36 citation statements)
references
References 21 publications
2
29
0
Order By: Relevance
“…Hyperlactaemia is strongly correlated with postoperative morbidity and mortality for patients undergoing complex open-heart surgery, especially children and infants [10,11]. The lactate is a marker of poor tissue perfusion and low cardiac output and can lead to metabolic acidosis.…”
Section: Introductionmentioning
confidence: 99%
“…Hyperlactaemia is strongly correlated with postoperative morbidity and mortality for patients undergoing complex open-heart surgery, especially children and infants [10,11]. The lactate is a marker of poor tissue perfusion and low cardiac output and can lead to metabolic acidosis.…”
Section: Introductionmentioning
confidence: 99%
“…1 Siegel et al observed that, in children admitted to the ICU after a cardiac surgery, high levels of lactate had a positive predictive value of 100% and a negative predictive value of 97% for death. 28 By using univariate logistic regression, Duke et al found that lactate allowed distinguishing survivors from nonsurvivors among children with sepsis at 12 and 24 hours of admission. 29 Hatherill et al suggest that hyperlactatemia can indicate death on admission and if it persists after 24 hours of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies [58][59][60][61] examined the prognostic value of blood lactate after congenital heart operations and they have found conflicting results, but agreed in the power of its serial determination 62 . Rossi and coworkers 62 postulate that elevated lactate levels might represent previous hemodynamic compromise, during or before operation, sometimes associated with liver dysfunction.…”
Section: Hemodynamic Assessment In Hlhsmentioning
confidence: 99%